The ABC of Governance Principles for Carbon Dioxide Removal Policy - Honegger, Matthias; Baatz, Christian; Eberenz, Samuel; Holland-Cunz, Antonia; Michaelowa, Axel; Pokorny, Benno; Poralla, Matthias; Winkler, Malte (Frontiers in Climate, 2022)
Climate change mitigation actions, including those aimed at developing and scaling carbon dioxide removal (CDR) activities spanning the industrial, energy, and agroforestry sector, emerge in a context of internationally shared norms that include governance objectives, legal provisions and informal expectations, and societal expectations. Established governance principles provide normative orientation for policy including when targeting the development, and scaling of CDR. Knowledge of these principles can guide effective discussion and evaluation of policy options. To facilitate discussion of mitigation options among experts and CDR practitioners, this study excerpts governance principles from legislative texts, the climate governance literature, and the CDR literature with relevance to CDR policy considerations. To illustrate the relevance of the governance principles found for evaluating policy options, we apply them to three technology groups of CDR: Bioenergy with Carbon Capture and Storage (BECCS), Direct Air Carbon Capture and Storage (DACCS), and forestry. This exercise indicates the importance of more intensive attention to the normative dimension of mitigation policies in ongoing deliberative and planning processes. Such efforts can help disentangle normative and factual dimensions and sources of (dis)agreement on the role of CDR in specific climate policy contexts.